Where are the women CEO's?: a study of the telecommunications industry in the U.S. & Finland - Rojas Levi, Elizabeth (2016)
As women make wide strides in labor participation in both, business and politics, a staggering reality is that the progress is rather minimal at the top of decision-making. In Nordic nations, which rank among the top five in the world for gender equality, women fare far worse than their American counterparts in the upper echelons of large corporations. For the Chief Executive Officer (CEO) position, the number one leadership and decision-making role in a company, women held 4.6% of CEO positions in S&P 500 companies in the US, while they held zero positions in large cap companies in Finland (Catalyst, 2015). The objective of this study is to gain an in-depth understanding of how women are disproportionally represented at the top decision-making position, the CEO post, in corporations. It also seeks to investigate the key factors that impact women’s career pathway to the CEO position in corporations and recommendations from participants to change the course. This study uses an exploratory framework employing a case study of the telecommunications industry, and compares the experiences of a Nordic country, Finland, with the United States, with an eye on the so-called Nordic Mystery (The Economist, 2014). Data was collected by conducting interviews with 11 participants in both countries, including CEOs and chief government decision-makers in the industry and leading experts in academia, business and international executive-search firms. This exploratory study poses limitations: a small number of participants in the sample, a reduced geographical context, short period of time for data collection, and findings applicable solely to the largest publicly traded firms. Contrary to most quantitative studies, however, this qualitative approach of interviewing current top decision-makers deepens the understanding of this phenomenon and serves as a starting point for future research of women CEOs.